Carbon emission from buildings: an application of life cycle assessment - Murnira Othman,; Ahmad Fariz Mohamed, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Buildings sector contribute to approximately 40% of carbon emissions, calling for the urge to tackle the problem. Carbon emission is mainly associated with the use of enormous amounts of energy during the operational phase in the building life cycle. Carbon emission from a building can be determined by measuring energy used starting from building material preparation until building’s end of life. There is a substantial literature on determining the embodied energy (EE) of materials and carbon emission especially using Life Cycle Assessment (LCA) which considers all stages in the building life cycle. The application of LCA provides a tool for complete measurement of building effects on the environment and indirectly contributes to mitigation measures that could be applied in the whole building construction process and building life cycle that would contribute to an environment friendly and effective built environment. Thus, this paper discusses the application of LCA in building sector to determine which phases in the building life cycle that consumes more energy and releases more carbon emission. The application of LCA is very appropriate in assessing the performance of a building where effective mitigation measures could be identified to improved efficiency and helping national energy and natural resource conservation.